Chemical composition and in vitro antibacterial activity of Pistacia terebinthus essential oils derived from wild populations in Kosovo. Issue 1 (December 2016) - Pulaj, Bledar; Mustafa, Behxhet; Nelson, Kate; Quave, Cassandra; Hajdari, Avni
Abstract Background Plant material from different organs ofPistacia terebinthus L., (Anacardiaceae) were collected in Kosovo with aim to analyze the chemical variability of the essential oils among native populations and to test them for potential antibacterial activity againstStaphylococcus aureus . Methods Essential oils obtained from leaves, pedicels, fruits and galls were analyzed by GC-FID and GC/MS. Minimum inhibitory concentration (MIC) against three clinically relevant strains ofS. aureus (NRS385, LAC and UAMS-1) were used to evaluate the antibacterial activity of essential oils. Results In total, 33 different compounds were identified. The main constituents were α-pinene (12.58–66.29 %), D-limonene (13.95–46.29 %), β-ocimene (0.03–40.49 %), β-pinene (2.63–20.47 %), sabinene (0.00–5.61 %) and (Z)-β-ocimene (0.00–44.85 %). Antibacterial testing of the essential oils against three clinical isolates ofS. aureus revealed that seven of the eight samples had some activity at the concentration range tested (0.04–0.512 % v/v). The gall tissues from both sites produced the highest yield of essential oil (3.24 and 6 %), and both exhibited growth inhibitory activity againstS. aureus . The most bioactive essential oils, which exhibited MIC90 values ranging from 0.032–0.128 % v/v, obtained from the fruits of the Ura e Shejtë collection site. Likewise, the leaf and pedicel essential oil from the same site was highly active with MIC90 values of 0.064–0.128 and 0.032–0.256 % v/v, respectively. Conclusions Principle Component Analyses demonstrated that there is a variation in the chemical composition of essential oil depending on the plant organs from which essential oil are obtained and the geographical origin of the plant populations. The highest variability regarding the chemical composition of essential oil was found between oils obtained from different organs originating from the Prizren site. The MIC90 activity ofPistacia terebinthus was on par or superior compared with Tea Tree Oil control (0.128 % v/v), suggesting that essential oils from this species may have some potential for development as an antibacterial agent forS. aureus infections.